2021
DOI: 10.1007/s42822-021-00068-w
|View full text |Cite
|
Sign up to set email alerts
|

A View on the Development and Current Situation of Behavior Analysis in Europe

Abstract: The present article discusses essential historical trends in behavior analysis in Europe, in terms of both organizations and conferences. Of particular interest is the series of the European Meetings on the Experimental Analysis of Behaviour held in different European cities between 1983 and 2000, just when the European Association for Behaviour Analysis (EABA) and the European Journal of Behavior Analysis (EJOBA) both started. This article not only extends the information on EABA and EJOBA from a previous pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although there are records of national progress of behavior analysis in some countries (Ala'i-Rosales et al, 2010;Hughes & Shook, 2007;Keenan et al, 2014a;Kelly et al, 2018), these mainly focus on dissemination of ABA rather than professional regulation. In terms of professional recognition, most European countries have used the standards and curricula set by the BACB as a starting point (Arntzen & Pellón, 2021). However, it is important for readers to understand that BACB standards did not equate to professional regulation in European jurisdictions.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are records of national progress of behavior analysis in some countries (Ala'i-Rosales et al, 2010;Hughes & Shook, 2007;Keenan et al, 2014a;Kelly et al, 2018), these mainly focus on dissemination of ABA rather than professional regulation. In terms of professional recognition, most European countries have used the standards and curricula set by the BACB as a starting point (Arntzen & Pellón, 2021). However, it is important for readers to understand that BACB standards did not equate to professional regulation in European jurisdictions.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) found that North Macedonia had more behavioral services available than the Czech Republic. Since the Czech Republic’s recent movement towards education in ABA, legislation, and improved dissemination (Arntzen and Pellón 2021 ), they have seemingly surpassed North Macedonia in ABA (with more parents having access to services and ABA knowledge, see Tables 1 and 3 ). Overall, this highlights the urgent need for legislative regulations of service centers to be trained in behavioral concepts, and to prepare preservice students with behavioral knowledge.…”
Section: Discussionmentioning
confidence: 99%